The Hippocratic oath and the ethics of medicine - Miles, Steven H. (OUP E-Books., 2005)
This engaging book examines what the Hippocratic Oath meant to Greek physicians 2400 years ago and reflects on its relevance to medical ethics today. Drawing on the writings of ancient physicians, Greek playwrights, and modern scholars, each chapter explores one of its passages and concludes with a modern case discussion. The Oath proposes principles governing the relationship between the physician and society and patients. It rules out the use of poison and a hazardous abortive technique. It defines integrity and discretion in physicians' speech. The ancient Greek medical works written during the same period as the Oath reveal that Greek physicians understood that they had a duty to avoid medical errors and learn from bad outcomes. These works showed how and why to tell patients about their diseases and dire prognoses in order to develop a partnership for healing and to build the credibility of the profession. Miles uses these writings to illuminate the meaning of the Oath in its day and in so doing shows how and why it remains a valuable guide to the ethical practice of medicine.; This is a book for anyone who loves medicine and is concerned about the ethics and history of this profession.